Implementasi Kerjasama Indonesia dan Malaysia terhadap Penanganan Pencucian Uang Berbasis Perdagangan Narkoba di Indonesia - Simamora, Tiurma Debora; Susiatiningsih, Hermini (Journal of International Relations, 2018)
This research aims to explain money laundering issues and describe the cooperationbetween Indonesia and Malaysia as Indonesia’s government effort to combat moneylaundering practices based drug trafficking in Indonesia. The cooperation is used as aform of optimizing the effort to overcome money laundering with exchanging financialintelligence information that is heavily guarded in secrecy with Malaysia. This researchis guided to neoliberal institusionalism framework. The research methodologes isqualitative method by using literature studies as the data source with analysis type ofdescriptive analysis. The result of this research are the cooperation was formed becauseit’s based on the same interests in combating money laundering, and the cooperation isenough to give results like quite a lot of drug seizures from drug smuggling fromMalaysia to Indonesia.